[Book review] Håkan Rydving & Konsta Kaikkonen eds., Religions around the Arctic - Joy, Francis (Journal of Northern Studies, 2024)
Review of: Håkan Rydving & Konsta Kaikkonen eds., Religions around the Arctic. Source Criticism and Comparisons (Stockholm studies in comparative religion 44), Stockholm: Stockholm University Press 2022